2011
DOI: 10.1007/s10620-011-1717-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of CXCL13 in Human Helicobacter pylori-Associated Gastritis

Abstract: The enhanced induction of CXCL13 may be involved in the pathogenesis of H. pylori-associated gastritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Recent studies have shown that CXCL13 and IL-10 were specific markers of CNS lymphoma [27]. Nakashima et al [28] reported significantly elevated CXCL13 expression levels in H. pylori-positive patients compared with those in uninfected controls. The CXCL13 expression levels also correlated with the degree of chronic gastritis and bacterial colonization observed.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that CXCL13 and IL-10 were specific markers of CNS lymphoma [27]. Nakashima et al [28] reported significantly elevated CXCL13 expression levels in H. pylori-positive patients compared with those in uninfected controls. The CXCL13 expression levels also correlated with the degree of chronic gastritis and bacterial colonization observed.…”
Section: Discussionmentioning
confidence: 99%
“…TLS resemble germinal centers of B cell follicles but lack a stable structural organization. They develop at target organs of chronic inflammatory autoimmune and infectious diseases and in the surroundings of solid tumors [5][6][7].…”
Section: Open Accessmentioning
confidence: 99%
“…High infiltration of CD20-positive cells has been observed in lymphoid follicles induced by H. pylori infection on immunohistochemistry. 52 No other B-cell-specific differentiation antigens have been expressed significantly more highly in pediatric antral NG than in NG-negative pediatric corpus tissue and adult AG tissue. Therefore, CD20 enrichment may result not only from a B-cell-abundant environment, but also from its role in the development of NG.…”
Section: Discussionmentioning
confidence: 96%
“…Given that CD20 is a B‐cell‐specific differentiation antigen present in most stages of B‐cell development, CD20 upregulation was expected to occur naturally in an environment rich in B cells such as GC and lymphoid follicles. High infiltration of CD20‐positive cells has been observed in lymphoid follicles induced by H. pylori infection on immunohistochemistry . No other B‐cell‐specific differentiation antigens have been expressed significantly more highly in pediatric antral NG than in NG‐negative pediatric corpus tissue and adult AG tissue.…”
Section: Discussionmentioning
confidence: 99%